Effects of balneotherapy and spa therapy on levels of cortisol as a stress biomarker: a systematic review - Antonelli, Michele; Donelli, Davide (International journal of biometeorology, 2018)
Balneotherapy and spa therapy are well-known practices, even though limited evidence has been produced about their biological effects. This systematic review primarily aims at assessing if balneotherapy, mud/peloid therapy, and spa therapy may influence cortisol levels. Secondarily, it aims at understanding if these interventions may improve stress resilience. PubMed/Medline, Embase, and Cochrane Library were searched for relevant articles in English or Italian about studies involving healthy and sub-healthy subjects or patients with a diagnosed disease about effects of balneotherapy, mud/peloid therapy, and spa therapy on serum and salivary cortisol levels. Fifteen studies involving 684 subjects were included. Five studies investigated biological effects of balneotherapy alone. Two of them reported significant changes of cortisol levels in healthy participants. The other three studies reported no significant variations in patients with rheumatic conditions. No studies investigated biological effects of mud/peloid therapy alone. Ten studies investigated biological effects of spa therapy with or without included mud/peloid therapy, and in all but two studies, significant variations of cortisol levels were reported. Our main findings suggest that balneotherapy may have the potential to influence cortisol levels in healthy subjects, in such a way as to improve stress resilience. Spa therapy with or without included mud/peloid therapy demonstrated the same potential to influence cortisol levels also in sub-healthy subjects and in patients with a diagnosed disease. Therefore, balneotherapy and spa therapy may be considered as useful interventions for the management of stress conditions. Further investigation is needed because of limited available data.